Description of the newly-hatched juvenile of Aegla castro Schmitt, 1942 (Crustacea, Anomura, Aeglidae) - Silva, Luane Samara Alves E; Guerrero-Ocampo, Cecilia Margarita; Negreiros-Fransozo, Maria Lucia; Teixeira, Gustavo Monteiro (Zootaxa, 2017)
This study describes and illustrates the morphology of the first juvenile stage of Aegla castro Schmitt, 1942. Ovigerous females were collected from May to July 2013, in Couro River (Mauá da Serra, Paraná, Brazil). These females were kept individually under controlled feeding, aeration, water temperature and quality and checked daily for hatching of juveniles. The newly-hatched juveniles were fixed in alcohol series and kept in 70% alcohol with glycerin in a 2:1 ratio prior to study under light microscopy. The newly-hatched juvenile of A. castro is the largest among aeglid species whose juveniles have been described. Aegla castro has asynchronous hatching. Some specimens were analyzed using scanning electron microscopy, revealing details of the setal morphology, some cephalothoracic appendages and lineae aeglicae. The number of setae in newly-hatched A. castro is lower than that described for other species, but does not appear to be diagnostic. However, A. castro is the only species described that combines the presence of four plumose setae on the third maxilliped exopod and 63–65 plumose setae on the maxilla exopod.